GIS Based Approach for Analysis of Habitat Suitability and wildlife conservation for African Buffaloes (Syncerus caffer) at Dhati Welel National Park, Ethiopia - Ketema Bahiru Tekalign (Journal of Wildlife, 2023)
Wildlife management is a crucial issue to maintain the sustainability of an ecosystem whereas habitat suitability analysis is very important for better conservation and management of species like the African Buffalo. Therefore, the effort of this study was to analyze habitat suitability for African Buffalo (Syncerus caffer) by employing GIS at Dhati Welel National Park, Ethiopia. The study employed five datasets include: land use land cover (LULC), elevation, slope, settlements, and rivers. In this study, the Analytic Hierarchy Process (AHP) and weight overlay analysis methods were applied using IDRISI 17 and ArcGIS 10.5 software. Each dataset was integrated using GIS and AHP to rate the individual classes of each factor and weigh the influence of one factor against the other, to determine the weighted contribution of importance to the habitat suitability. As result, the consistency ratio was 0.03 and found with acceptable limits. Then, the weighted overlay tool was applied to calculate the final habitat suitability map of the African Buffalo based on the influence value. The result indicates, 35.3 % (362.7 km2) of the study area was optimal for the African Buffalo habitat. Therefore, according to the results of the finding more areas of Dhati Welel National Park are suitable for the African Buffalo habitat based on the factors employed in this study. So that, this indicates the area is important for conservation from habitat loss and fragmentation.
Keywords: African Buffalo